A Comprehensive Analysis of Symmetric Arginine Dimethylation in Colorectal Cancer Tissues Using Immunoaffinity Enrichment and Mass Spectrometry. Issue 15 (2nd July 2020) - Lim, Yongchul; Park, Yae Eun; Ha, Sujin; Lee, Ji Eun; Kim, Hee Cheol
Abstract: Protein arginine methyltransferase 5 (PRMT5) is a major enzyme responsible for generating monomethyl and symmetric dimethyl arginine in proteins. PRMT5 is essential for cell viability and development, and its overexpression is observed in a variety of cancers. In the present study, it is found that levels of PRMT5 protein and symmetric arginine dimethylation in colorectal cancer (CRC) tissues are increased compared to those in adjacent noncancerous tissues. Using immunoaffinity enrichment of methylated peptides combined with high‐resolution mass spectrometry, a total of 147 symmetric dimethyl‐arginine (SDMA) sites in 94 proteins are identified, many of which are RNA binding proteins and enzymes. Quantitative analysis comparing CRC and normal tissues reveals significant increase in the symmetric dimethylation of 70 arginine sites in 46 proteins and a decrease in that of four arginine sites in four proteins. Among the 94 proteins identified in this study, it is confirmed that KH‐type splicing regulatory protein is a target of PRMT5 and highly expressed in CRC tissues compared to noncancerous tissues. This study is the first comprehensive analysis of symmetric arginine dimethylation using clinical samples and extends the number of known in vivo SDMA sites. The data obtained are available via ProteomeXchange with the identifier PXD015653.